Pengaruh Diversitas Gender Dewan Direksi dan Komite Audit terhadap Pengungkapan Integrated Reporting pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2021-2023 - Erryna Putri Amanda; Fajar Gustiawaty Dewi (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study aims to analyze the effect of gender diversity in the board of directors and the presence of an audit committee on the level of integrated reporting disclosure in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The study uses companies' annual reports as secondary data and applies multiple linear regression for analysis. The results show that both gender diversity and the audit committee have a positive and significant effect on integrated reporting disclosure. These findings support agency theory, which posits that sound corporate governance enhances transparency and reporting accountability. This research contributes theoretically to the literature on integrated reporting and offers practical implications for companies in formulating more sustainable and informative reporting strategies.